Одна по следу хищника: роман / Лев Дворецкий - Дворецкий Лев Семенович (Честь и сила, 1998)
Экземпляры: ф.2 (2007) / Инвентарный номер: 51264 / Цена: / Сис.шифр: 84(2Рос=Рус)6-4 / Авт.знак: Д 24 / ГРНТИ: 17.82.31 / ББК: 84(2Рос=Рус)6-44